2016
DOI: 10.5603/cj.a2016.0094
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing-guided percutaneous transcatheter closure of secundum atrial septal defect with rim deficiency: First-in-human series

Abstract: (Cardiol J 2016; 23, 6: 599-603)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…printing-guided percutaneous transcatheter closure of secundum ASD with rim deficiency in six patients [10]. This was followed by a report by Zhu et al in patients with multiple secundum ASD [11] and finally by Velasco Forte et al in patients with superior sinus venosus ASD and partial anomalous pulmonary venous drainage [12].…”
Section: Discussionmentioning
confidence: 94%
“…printing-guided percutaneous transcatheter closure of secundum ASD with rim deficiency in six patients [10]. This was followed by a report by Zhu et al in patients with multiple secundum ASD [11] and finally by Velasco Forte et al in patients with superior sinus venosus ASD and partial anomalous pulmonary venous drainage [12].…”
Section: Discussionmentioning
confidence: 94%
“…Typically, this category refers to a defect in the sinus venosus component of the atrial septum, that results in a pathologic communication between the right and left atrium in conjunction with anomalous systemic or pulmonary venous drainage. Less commonly, this can also describe a coronary sinus septal defect (unroofed coronary sinus) as well as device evaluation in secundum ASDs with deficient rims [ 4 , 7 , 15 ] or in the presence of multiple ASDs [ 14 ]. There is substantial qualitative support [ 4 – 17 ] for 3D printing for ASDs with additional complexity especially for interventional planning.…”
Section: Discussionmentioning
confidence: 99%
“…Valverde et al [9] extended the use of 3DPSP to the field of transcatheter cardiovascular interventions and reported 3DPSP being a valuable adjunct in planning and simulating endovascular stenting in transverse aortic arch hypoplasia. Following this approach, feasibility of 3DPSP to identify the optimal prosthesis in terms of size for transcatheter closure of atrial septal defect or patent ductus arteriosus was demonstrated [10,11]. Also, 3DPSP can enrich patient counselling [12][13][14] and affect clinical decision making [15].…”
Section: Congenital Heart Diseasementioning
confidence: 99%